Kekuatan Modal dan Perilaku Kekerasan Negara Pada Masa Orde Baru dan Pasca Orde Baru: Studi Kasus Freeport - , Adrianus Bintang Hanto Nugroho ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research entitled âCapital Power and State Violence Behavior in The New Order and Post New Order Eras : Freeport Case Studyâ is to explain how Freeport as a capital power may possibly affects various acts of violence perpetrated by the State. During the New Order era, state provided physical protection against Freeport by taking the Amungme communal land, in favor of mining interests. Various acts of objection have been made by the Amungme people concerning Freeport's presence in their communal land, but then countered with violence by the state. State violence behaviors persist as yet, even after the fall of the New Order. However, targets of violence are no longer people of Amungme but shifted to the traditional gold miners and Freeportâs laborers. The author uses the state theory by Ralph Miliband to explain how the power of capital of Freeport could affect stateâs violence behavior. According to the Miliband, capitalist class (capital power or corporation) with their economic power is able to use the state as an instrument to fulfill their interests. By colonizing the state elites, corporations can influence the policyâs formation to fit their interests. In the context of Freeport, colonization is made through building a close relation with the state elites. This close relation is built in two different ways. During the New Order era, Freeport was tend to take a more subjective approach by building a good personal relations with the state's elite, financing their holiday cost, and making business deals to make them rich. Meanwhile, in the post-New Order era, Freeport is tend to take a more objective approach by making official payments through the Corporate Social Responsibility (CSR) programs and even funding the development projects in Mimika, Papua. The fall of the New Order era, had forced Freeport to modify their pattern approach, from subjective into more objective. It shows that the capitalist class, in form of corporations, is able to adapt to the state systemâs changes. Neither on the authoritarian nor democratic system, the capitalist class is in fact can rule the state, even though they do not govern it directly.